Evaluation of opening pattern and bone neoformation at median palatal suture area in patients submitted to surgically assisted rapid maxillary expansion (SARME) through cone beam computed tomography (Journal of Applied Oral Science, 2015)
AbstractSurgically assisted rapid maxillary expansion (SARME) is the treatment of choice to adult patients even with severe transversal maxillary discrepancies. However, the adequate retention period to achieve the bone remodeling, thus assuring treatment stability, is controversial.Objective To evaluate the opening pattern and bone neoformation process at the midpalatal suture in patients submitted to surgically assisted (SARME) through cone beam computed tomography (CBCT).Material and Methods Fourteen patients were submitted to SARME through subtotal Le Fort I osteotomy. Both the opening pattern and the mean bone density at midpalatal suture area to evaluate bone formation were assessed pre- and post-operatively (15, 60 and 180 days) through CBCT.Results Type I opening pattern (from anterior to posterior nasal spine) occurred in 12 subjects while type II opening pattern (from anterior nasal spine to transverse palatine suture) occurred in 2 individuals. The 180-day postoperative mean (PO 180) of bone density value was 49.9% of the preoperative mean (Pre) value.Conclusions The opening pattern of midpalatal suture is more related to patients’ age (23.9 years in type I and 33.5 years in type II) and surgical technique. It was not possible to observe complete bone formation at midpalatal suture area at the ending of the retention period studied (180 days).